PENGARUH PEMBERIAN EKSTRAK DAUN KEPEL (Stelechocarpus burahol) SEBAGAI FEED ADDITIVE HERBAL TERHADAP RETENSI NITROGEN DAN AMONIA EKSKRETA AYAM BROILER - Riki Saumi Nuryana; Abun Abun; Eulis Tanti Marlina (Jurnal Ilmu dan Teknologi Peternakan, 2021)
The purpose of this study was to determine the effect of giving Kepel (Stelechocarpus burahol) leaf extract to nitrogen retention and ammonia excretion of broiler chickens at the end of maintenance. This study used 100 Day Old Chick (DOC) broilers with a maintenance period of 30 days. The ration was derived from ingredients compiled into basal feed containing PK 21.50% and EM 3032 cal / g. The experimental design used was a Completely Randomized Design (CRD), the treatment of 4 doses of Kepel leaf extract in rations was repeated 5 times. The treatment given in the ration consisted of R0 = 0%, R1 = 0.15%, R2 = 0.30%, and R3 = 0.45%. The parameters observed were nitrogen retention and ammonia value of broiler chicken excreta. The research data were processed using statistical analysis of variance and continued with the Duncan Test to see the significance of the inter-treatments. The results showed that the administration of 0.30% kepel leaf extract during the maintenance period resulted in the highest nitrogen retention value and the lowest ammonia content in broiler chicken excreta.